IDENTIFICATION AND INVENTORY OF CASSAVA (Manihot esculenta Crantz) IN NORTH SUMATERA - Emmy Harso Kardhinata; Edison Purba; Dwi Suryanto; Herla Rusmarilin (Universitas Medan Area, 2020)
The study of identification and inventory of cassava accessions was done from August to September 2014 in four districts based on their potential as a center for cassava cultivation, namely Simalungun, Serdang Bedagai, Deli Serdang, Langkat Regency representing the lowlands and Simalungun and Karo Regency representing the highlands. Each district was selected 3 subdistricts and each subdistrict was surveyed 3 villages randomly through the accidental sampling method. Guidance on identifying morphological characters was used by reference from Fukuda, et al. (2010) by giving a score for each character observed. The results of the study obtained 8 genotypes with their respective codes and local names; 1) Sawit (G1), 2) Lampung (G2), 3) Merah (G3), 4) Adira-1 (G4), 5) Kalimantan (G5), 6) Malaysia (G6), 7) Roti (G7) and 8) Klanting (G8). The most common genotype found in the location were Malaysia and Adira-1, while the rarest was Merah. The yield potential at the age of 10 months were Sawit (26,9–30,1 tons/ha), Lampung (29,6–52,6 tons/ha), Merah (54–61,6tons/ha), Adira-1 (34,8–55,0 tons/ha), Kalimantan (15,8–64,2 tons/ha), Malaysia (32,9–64,3 tons/ha), , Roti (24,7–55,5 tons/ha), and Klanting (327,4–49,8 tons/ha).